Porphyrin Hetero-Trimer Involving a Hydrophilic and a Hydrophobic Structure with Application in the Fluorescent Detection of Toluidine Blue - Anca Lascu; Camelia Epuran; Ion Fratilescu; Mihaela Birdeanu; Liliana Halip; Eugenia Fagadar-Cosma (Chemosensors, 2022)
The combination of a metallated porphyrin, Pt(II)-5,10,15,20-tetrakis-(4-allyloxyphenyl)-porphyrin (Pt-allyloxyPP), and a water-soluble porphyrin, 5,10,15,20-tetrakis(4-sulfonatophenyl)-porphyrin (TSPP), leads to the formation of a porphyrin hetero-trimer. The hetero-trimer, consisting of two TSPP molecules linked via oxygen atoms axially to the platinum atom in the Pt-allyloxyPP molecule, was characterized by UV–Vis, FT-IR, fluorescence, and 1H-NMR spectroscopy, and the proposed structure was confirmed. The new porphyrin hetero-trimer offers both the advantage of enhanced fluorescence and the presence of multiple sites for the detection of toluidine blue, due to its high affinity for acidic binding sites. This work brings attention to the purposely designed fluorescent sensor for toluidine blue, in the biologically relevant concentration domain of 1.9 × 10−6–6.39 × 10−5 M, with a very good accuracy.